2002
DOI: 10.1103/physrevlett.89.077202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure, Phase Diagram, and a New Type of Spin-Flop Transition Dominated by Higher Order Interaction in a Localized5fSystemU3Pd

Abstract: The magnetic structure of the localized-5f uranium intermetallic compound U 3 Pd 20 Si 6 has been determined by means of a neutron diffraction experiment. Our data demonstrate that this compound has a collinear coupling of the sublattice ordering of the uranium spins on the 4a and 8c sites. We conclude that higher-order exchange and/or quadrupole interactions are necessary to stabilize this unique collinear structure. We discovered a new type of spin-flop transition against the uniaxial anisotropy induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The cerium and uranium intermetallic compounds have been investigated by a number of workers because of their unusual and interesting physical properties [1][2][3][4][5][6][7][8][9]. These properties arise from the strongly correlated nature of the 4f and 5f electrons and their hybridization with the conduction electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The cerium and uranium intermetallic compounds have been investigated by a number of workers because of their unusual and interesting physical properties [1][2][3][4][5][6][7][8][9]. These properties arise from the strongly correlated nature of the 4f and 5f electrons and their hybridization with the conduction electrons.…”
Section: Introductionmentioning
confidence: 99%
“…1 are the calculated results based on the CEF level scheme and the mean-field approximation. In R 3 Pd 20 X 6 , neutron diffraction experiments demonstrated that the magnetic ordering at the 4a and 8c sites occurs independently at different temperatures [15][16][17]. Furthermore, the CEF level schemes of the 4a and 8c sites in Pr 3 Pd 20 Ge 6 are different.…”
mentioning
confidence: 99%
“…The R atoms occupy two crystallographically inequivalent sites: 4a sites with O h symmetry, and 8c sites with T d symmetry. R 3 Pd 20 X 6 have attracted much attention because of their characteristic magnetic ordering with two different propagation vectors on two sublattices, and the quadrupole ordering of f electrons [15][16][17][18][19]. In particular, R 3 Pd 20 Ge 6 have been studied intensively from the viewpoint of rattling motions of a guest rare-earth ion in an oversized cage that are not observed in R 3 Pd 20 Si 6 [20,21].…”
mentioning
confidence: 99%